Closing the Umbrella: A Call for Nation-Specific Indigenous Scholarship - Forsythe, Laura; Markides, Jennifer; Delgado, Lucy (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2025)
Indigenous umbrella scholarship speaks about Indigenous Peoples, knowledges, and cultures as a monolith instead of recognizing the specific Indigenous nations from which these peoples, knowledges, and cultures come. Indigenous umbrella scholarship was long a necessity due to the scarcity of nation-specific scholarship. In recent years, Indigenous scholars have made strides in the academy to legitimize our communities’ knowledges and practices. As three Métis scholars, we argue that we have reached a tipping point in the movement toward nation-specific work, and we offer three recommendations to scholars writing with, for, and about Indigenous Peoples.